Adverse Childhood Experiences and Substance Use History among Vulnerable Older Adults Living in Public Housing. Issue 6 (3rd October 2017) - Larkin, Heather; Aykanian, Amanda; Dean, Erica; Lee, Eunju
ABSTRACT: Previous research shows strong correlations between adverse childhood experiences (ACE) and later life health. The current study examines the relationship between ACEs and substance use among older adults living in public housing. Results show that about one-third of participants had four or more ACEs, and ACE score predicted likelihood of substance use history. Over half of older adults with four or more ACEs experienced substance abuse in their lifetime compared to one out of ten older adults with less than four ACEs. Findings shed light on a vulnerable group and point to next steps in research and practice.